Effects of Carbon Dioxide and Temperature on the Oxygen-Hemoglobin Dissociation Curve of Human Blood: Implications for Avalanche Victims - Woyke, Simon; Brugger, Hermann; Ströhle, Mathias; Haller, Thomas; Gatterer, Hannes; Dal Cappello, Tomas; Strapazzon, Giacomo (Frontiers in Medicine, 2022)
Complete avalanche-buried patients are frequently exposed to a combination of hypoxia and hypercapnia with a risk of normothermic cardiac arrest. Patients with a long burial time and an air pocket are exposed to a combination of hypoxia, hypercapnia and hypothermia that may lead to the development of the “triple H syndrome”. This specific combination has several pathophysiological implications, particularly on the cardiovascular system and oxygen transport (oxygen supply and oxygen consumption). To examine the effects on hemoglobin oxygen affinity we investigated venous blood samples from 15 female and 15 male healthy subjects. In a factorial design of four different carbon dioxide partial pressure (PCO2) levels (20, 40, 60, and 80 mmHg) and five different temperature levels (13.7, 23, 30, 37, and 42 °C), 30 unbuffered whole blood samples were analyzed in a newly developed in-vitro method for high-throughput oxygen dissociation curve (ODC) measurements. P50s, Hill coefficients, CO2-Bohr coefficients and temperature coefficients were analyzed using a linear mixed model. Mean P50 at baseline (37 °C, 40 mmHg PCO2) was 27.1 ± 2.6 mmHg. Both, CO2-Bohr coefficient (p<0.001) and temperature coefficient (p<0.001) had a significant effect on P50. The absolute CO2 effect was still pronounced at normothermic and febrile temperatures, whereas at low temperatures the relative CO2 effect (expressed by CO2-Bohr coefficient; p<0.001, interaction) was increased. The larger impact of PCO2 on oxygen affinity at low temperature may be caused by the competition of 2,3-BPG with PCO2 and the exothermic binding characteristic of 2,3-BPG. In a model of an avalanche burial, based on published data of CO2 levels and cooling rates, we calculated the resulting P50 for this specific condition based on the here reported PCO2 and temperature effect on ODC. Depending on the degree of hypercapnia and hypothermia, a potentially beneficial increase in hemoglobin oxygen affinity in the hypoxic condition might ensue.